الإدارة الالكترونية وعلاقتها بإدارة المعرفة من وجهة نظر موظفي مؤسسات الأعمال في شرقي القدس - حسين خليل, عبد القادر (جامعة الوادي - University of Eloued, 2019)
هدفت الدراسة التعرف إلى واقع تطبيق الإدارة الالكترونية في مؤسسات الأعمال في شرقي القدس، معرفة مستوى تطبيق إدارة المعرفة فيها، والتعرف إلى المعيقات التي تواجه الإدارة الالكترونية وعلاقتها بإدارة المعرفة في مؤسسات الأعمال في شرقي القدس. وقد تم استخدام المنهج الوصفي في الدراسة، توصلت الدراسة إلى مجموعة من النتائج كان أهمها: الإدارة الإلكترونية توفر نظام أرشفة إلكتروني لمختلف الأطراف، وتعمل على توفير البيانات لدى جميع المستفيدين، وتسهم في الاستغلال الأمثل للموارد المتاحة للمؤسسة، أن المؤسسة تعتمد في تخزين المعرفة واسترجاعها على الأرشيف الورقي، وتهتم بتطبيق المعرفة على كل المشكلات لتتمكن من تجاوزها، وتهتم بالحصول على المعرفة المتطورة من المصادر الخارجية، أن أهم المعيقات التي تواجهها المؤسسة هي: روتينية الإجراءات الإدارية المتبعة في المؤسسة، وخوف الإدارة على سریة بعض المعلومات، وندرة الدورات التدريبية في مجالي الإدارة الالكترونية وإدارة المعرفة، وغموض مفهوم الإدارة الالكترونية لدى بعض القيادات الإدارية، وسيطرة المركزية على عملية القرار في الإدارة، والطبيعة البشرية وثقافة الأبواب المغلقة، وصعوبة أرشفة الأعمال التقليدية المتراكمة إلكترونياً، ونقص الكوادر البشرية المتخصصة The study aimed to identify the reality of the application of electronic management in business enterprises in East Jerusalem, knowledge of the level of application of knowledge management, and identify the obstacles facing electronic management and its relationship to knowledge management in business enterprises in East Jerusalem. The descriptive approach was used in the study, The study reached a number of results, the most important of which was: e-management provides an electronic archiving system for all parties, provides data to all beneficiaries, and contributes to the optimal utilization of resources available to the institution. The institution relies on storing the knowledge and retrieving it on paper archives. Problems to be overcome, and interested in obtaining advanced knowledge from external sources, the most important obstacles faced by the institution are: Routine administrative procedures followed by the institution, and the fear of the management of the confidentiality of some information, and the scarcity of training courses in the areas of Emanagement and knowledge management, and the ambiguity of the concept of electronic management of some administrative leaders, the central control of the decision in management, human nature and the culture of closed doors, and the difficulty of archiving the traditional backlog electronically, and the lack of specialized human resources.
مقال
Keywords: لإدارة الالكترونية ; إدارة المعرفة; Electronic Management ; Knowledge Management